2011
DOI: 10.1007/s10549-011-1928-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I–II study of vorinostat plus paclitaxel and bevacizumab in metastatic breast cancer: evidence for vorinostat-induced tubulin acetylation and Hsp90 inhibition in vivo

Abstract: Purpose In preclinical models, the histone deacetylase inhibitor vorinostat sensitizes breast cancer cells to tubulin polymerizing agents and to anti-vascular endothelial growth factor (VEGF) directed therapies. We sought to determine the safety and efficacy of vorinostat plus paclitaxel and bevacizumab as first-line therapy in metastatic breast cancer (MBC), and the biological effects of vorinostat in vivo. Patients and Methods Fifty-four patients with measurable disease and no prior chemotherapy for MBC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Considering the pleiotropic effects of HDAC inhibitors against malignant tumors, their true therapeutic potential most likely lies in combinations with other anticancer drugs (24). Recent clinical trials have indicated that HDAC inhibitors enhance the antitumor activities of several conventional chemotherapeutic and molecular-target drugs (25)(26)(27). Additionally, a previous study showed that HDACs were highly expressed in RCC, suggesting that HDAC inhibitors may be effective on RCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pleiotropic effects of HDAC inhibitors against malignant tumors, their true therapeutic potential most likely lies in combinations with other anticancer drugs (24). Recent clinical trials have indicated that HDAC inhibitors enhance the antitumor activities of several conventional chemotherapeutic and molecular-target drugs (25)(26)(27). Additionally, a previous study showed that HDACs were highly expressed in RCC, suggesting that HDAC inhibitors may be effective on RCC (28).…”
Section: Discussionmentioning
confidence: 99%
“…For the primary efficacy analysis in 44 patients treated at with this SAHA dose, the objective response rate was 55% and SAHA was found to induce tubulin acetylation and Hsp 90 inhibition [28]. …”
Section: Discussionmentioning
confidence: 99%
“…ORR was 24 out of 54 (55%). [61] Histone deacetylases are crucial components of the oestrogen receptor transcriptional complex. In a preclinical model, HDACI could reverse tamoxifen/aromatase inhibitor resistance in hormone receptor-positive breast cancer.…”
Section: Trials Of Vorinostat In Solid Tumors -Combination Therapymentioning
confidence: 99%